Loss of proton‐sensing GPR4 reduces tumor progression in mouse models of colon cancer - Leonie Perren; Moana Busch; Pedro A. Ruiz; Ermanno Malagola; Valeria Baumeler; Federica Foti; Adelina Gross; Tobias Grütter; Hendrik Edel; Cordelia Schuler; Kristina Handler; Glenn De Lange; et al. (Molecular Oncology)
We aimed to understand the role of G protein‐coupled receptor 4 (GPR4) in tumorigenesis. GPR4 is a pH‐sensing receptor that is activated by acidic extracellular pH. GPR4 is expressed primarily in vascular endothelial cells (ECs). Intestinal tissue from patients with inflammatory bowel disease (IBD) shows increased expression of GPR4. Patients with IBD have a significantly increased risk of developing colorectal cancer (CRC). In the MC38 model, Gpr4‐deficient mice showed significantly reduced tumor size and weight compared to wild‐type (WT) mice. This effect correlated with a significant increase in IL2 protein and natural killer (NK)1.1+ cells in tumor tissue in Gpr4−/− compared to WT. In the azoxymethane (AOM)/dextran sodium sulfate (DSS) model of CRC, Gpr4‐deficient mice showed significantly reduced tumor progression and number of apurinic/apyrimidinic (AP) sites. Gpr4‐deficient mice showed a significantly increased number of NKp46+ cells in tumor tissue, and increased numbers of NK cells were confirmed by qPCR and flow cytometry. The absence of GPR4 significantly attenuated tumor progression in the colon of mice, and this result correlated with increased cytotoxic cell activity and reduced presence of tumor‐associated macrophages and neutrophils. GPR4 represents a potential new target for therapeutic intervention.